2019
DOI: 10.1016/j.ctro.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Whole-ventricular irradiation for intracranial germ cell tumors: Dosimetric comparison of pencil beam scanned protons, intensity-modulated radiotherapy and volumetric-modulated arc therapy

Abstract: Background: Whole-ventricular radiotherapy (WV-RT) followed by a boost to the tumor bed (WV-RT/TB) is recommended for intracranial germ cell tumors (IGCT). As the critical brain areas are mainly in the target volume vicinity, it is unclear if protons indeed substantially spare neurofunctional organs at risk (NOAR). Therefore, a dosimetric comparison study of WV-RT/TB was conducted to assess whether proton or photon radiotherapy achieves better NOAR sparing. Methods: Eleven children with GCT received 24 Gy(RBE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…Boehling compared mean and maximum doses to vascular structures of the circle of Willis between PBT (with both 3D-PBT and IMPT) and IMRT, confirming the dosimetric advantages of protons [10]. In the study by Correia, only the mean dose to the circle of Willis was reduced by PBT as compared to IMRT and VMAT [11].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Boehling compared mean and maximum doses to vascular structures of the circle of Willis between PBT (with both 3D-PBT and IMPT) and IMRT, confirming the dosimetric advantages of protons [10]. In the study by Correia, only the mean dose to the circle of Willis was reduced by PBT as compared to IMRT and VMAT [11].…”
Section: Resultsmentioning
confidence: 92%
“…Globally, three studies [11, 14, 17] provided useful dosimetric data for extracranial OARs of the cephalic district: mean left lens dose, maximum left lens doses, and mean doses to lacrimal glands were significantly improved in PBT plans (Figure 5). Three supplementary studies [15, 18, 19] assessed dosimetry of cervical, thoracic, and abdominal OARs: mean doses to the esophagus, thyroid, lungs, and liver were significantly improved with PBT, while no significant overall advantage for the kidneys was observed ( P =0.11) (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for very complex target volumes ( Figure 2) involving large parts of the brain, such in whole-ventricular RT for intracranial germ cell tumours, a dosimetric comparison study showed an approximately one-third reduction in integral dose to the brain, and also a better sparing of the circle of Willis with PT. 11 This may be clinically significant, as radiation dose delivered to the circle of Willis was recently proposed as the best predictor of stroke in childhood brain cancer survivors. 12 Moreover the dosimetric advantage is particularly striking for large target volumes, such in the case of craniospinal irradiation (CSI), where PT is able to completely spare OARs anterior to the vertebrae, as it is demonstrated in Figure 1b.…”
Section: Proton Beam Therapy For Brain Tumoursmentioning
confidence: 99%